The Feasibility and Acceptability of The Girls Peer Activity (G-PACT) Peer-led Mentoring Intervention - Michael B. Owen; Charlotte Kerner; Sarah L. Taylor; Robert J. Noonan; Lisa Newson; Maria-Christina Kosteli; Whitney B. Curry; Stuart J. Fairclough (MDPI AG, 2018)
Enjoyment of physical activity (PA) is positively correlated with PA engagement. The inclusion of peers has been found to increase the likelihood of PA enjoyment in youth. Peer-led strategies, incorporating peer networks in the intervention delivery, is relatively underused and consequently understudied in school-based PA interventions. The purpose of this investigation was to evaluate the feasibility and acceptability of the novel Girls Peer Activity (G-PACT) peer-led mentoring intervention. Two-hundred and forty-nine Year 9 adolescent girls (13–14 years old) from three mixed-sex secondary schools located in West Lancashire, North-West England were invited to participate in the G-PACT project. The study employed a novel approach by using a three-tier model, including (Tier 1) Mentors (undergraduate students), (Tier 2) Leaders (Year 9 girls selected by teachers), and (Tier 3) Peers (whole Year 9 cohort). Mentors delivered a series of educational and leadership training to the Leaders in each respective school who then disseminated this information to their Peers and encouraged them to engage in more physical activities. Eight focus groups were conducted with Leaders (n = 40), 28 focus groups with Peers (n = 185), two focus groups with Mentors (n = 6), and three interviews with teachers (n = 4). Thematic analysis was used to analyze the pooled data and identify the key themes. The study found that the G-PACT intervention was feasible and acceptable for adolescent PA Leaders and their Mentors. The relationship between Leaders and their Peers required refinement to improve the communication processes to increase Peer engagement in the G-PACT project.